دراسة بعض خواص الترب المتشكلة على الصخور الرملية الكلسية في منطقتي برج اسلام والشامية (اللاذقية) وتصنيفها - رقية, عادل; غانم, سمر (Latakia University Journal -Biological Sciences Series, 2020)
This research, which was conducted during the year 2018, aims to identify some of the properties of the soils formed on the limestone rocks scattered in the Lattakia region as part of a comprehensive study includes study the diagnostic properties of pedological covert in the area of Lattakia and its classification. To achieve the objectives of this research Soil profiles were described and studied according to the common methods used worldwide in morphological study of the soil profile. The soil samples were collected from the described horizons in a systematic manner. Some physical and chemical analysis of the soil and the original materials were carried out in addition to the micro-morphological study of the parent materiel. The study of the Morphological characteristics of the profiles, showed poorly developed and still in the early stages of soil formation .Also ,the General chemical analysis showed a difference between the two profiles in terms of the chemical structure, despite the similarity of the original material, under the influence of a number of factors, the most important of which is the histological site.The results of the morphological study showed that the constituents of, the parent material affect not only soil composition but also the degree and quality of weathering products All in all, according to the American soil classification the soil can be classified as follows:( order- suborder - Grets Groups) P1: Entisols , Fluvents , Xerofluvents. P2: Entisols , Orthents , Xerorthents . يهدف هذا البحث الذي أجري في العام2018 م, إلى تحديد بعض خصائص الترب المتشكلة على الصخور الرملية الكلسية المنتشرة في منطقة اللاذقية كجزء من دراسة شاملة تتضمن دراسة الخواص التشخيصية للغطاء البيدولوجي في منطقة شمال شرق منطقة اللاذقية والمساهمة في تصنيفه. ولتحقيق أهداف البحث, حضرت المقاطع ووصفت اعتماداً على الطرق المتبعة عالمياً في الدراسة المورفولوجية للتربة ثم جمعت العينات من الآفاق بطريقة منهجية وأجريت عليها بعض التحاليل الفيزيائية والكيميائية للعينات الماخوذة و التحليل الكيميائي العام للتربة ومواد الأصل بالإضافة إلى الدراسة الميكرومورفولوجية للصخر الأم. أظهرت نتائج دراسة الخصائص المورفولوجية أن المقاطع ضعيفة التطور وفي المراحل الأولى لتشكل التربة, كما بين التحليل الكيميائي العام اختلاف المقطعين من ناحية التركيب الكيميائي بالرغم من تشابه مادة الأصل, وذلك تحت تاثير عدد من العوامل من أهمها الموقع التضاريسي, كما أظهرت نتائج الدراسة الميكرومورفولوجية تأثير المعادن المكونة للصخر الأم في تركيب التربة وفي درجة وتوعية نواتج التجوية. خلص البحث وبالإعتماد على نتائج كافة التحاليل إلى تصنيف المقاطع المدروسة وحسب التصنيف الامريكي إلى المستويات التصنيفية التالية : (رتبة-تحت رتبة- مجموعة). المقطع (: (P1 رتبة Entisols - تحت رتبة : Fluvents مجموعة : Xerofluvent . المقطع (P2) : رتبة Entisols تحت رتبة : Orthentsمجموعة : xerorthents .